2010
DOI: 10.1371/journal.pone.0015518
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Germline Transmission of Cultured Avian Primordial Germ Cells

Abstract: BackgroundAvian primordial germ cells (PGCs) have significant potential to be used as a cell-based system for the study and preservation of avian germplasm, and the genetic modification of the avian genome. It was previously reported that PGCs from chicken embryos can be propagated in culture and contribute to the germ cell lineage of host birds.Principal FindingsWe confirm these results by demonstrating that PGCs from a different layer breed of chickens can be propagated for extended periods in vitro. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
169
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(182 citation statements)
references
References 61 publications
(85 reference statements)
2
169
0
5
Order By: Relevance
“…At this time, chicken PGCs can be successfully maintained in vitro without the loss of germ cell integrity (32,33), and generating transgenic chickens is feasible using transposon elements in cultured chicken PGCs (18,34). This study demonstrated the creation of specific knockout chickens using TALENs.…”
Section: Discussionmentioning
confidence: 91%
“…At this time, chicken PGCs can be successfully maintained in vitro without the loss of germ cell integrity (32,33), and generating transgenic chickens is feasible using transposon elements in cultured chicken PGCs (18,34). This study demonstrated the creation of specific knockout chickens using TALENs.…”
Section: Discussionmentioning
confidence: 91%
“…S2). Only male SNUhp26 PGC-transplanted roosters were test-crossed because the reverse-sexed chimeras failed to produce donor-derived offspring and the efficiency of germ-line transmission was quiet low compared with those of the single-sex chimeras of previous reports (1,3,15). Among the donor PGC-derived progenies, the transgenic chicks could be easily identified with a fluorescent excitation lamp and the detection filters because of strong GFP expression in all transgenic chick tissues, including the beak, feather pulp, feet, and muscle ( Fig.…”
Section: Characterizations After Transfection and G418-selection Of Cmentioning
confidence: 99%
“…Choi et al (2) reported 12.5-82.6% (49.0% on average) germ-line transmission by transferring mixed PGCs, and Macdonald et al (3) estimated that the frequency of donor-derived sperm was 1-30% in the semen of recipient roosters, even though the endogenous PGCs of recipient embryos were depleted by irradiation. The frequencies in these previous reports were similar to the rates of germ-line transmission obtained from chimeras after the transfer of freshly isolated or short-term cultured PGCs (15,16).…”
Section: Characterizations After Transfection and G418-selection Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken as an acceptance model organism (Cogburn et al 2007) have advantages of population distribution and samples can be obtained easily. PGCs have been obtained mainly from germinal crescent (Petitte et al 1990, Park andHan 2012) and embryonic blood (van de Lavoir et al 2006, Macdonald et al 2010, Miyahara et al 2014, Naito et al 2015. However, their numbers have been quite limited (Park et al 2003) and couldn't provide sufficient materials for the transgenic manipulation (Shiue et al 2009).…”
Section: Introductionmentioning
confidence: 99%